2021
DOI: 10.5006/3844
|View full text |Cite
|
Sign up to set email alerts
|

Significance of π–Electrons in the Design of Corrosion Inhibitors for Carbon Steel in Simulated Concrete Pore Solution

Abstract: Chloride–induced corrosion of carbon steel reinforcements is one of the most important failure mechanisms of reinforced concrete structures. Organic corrosion inhibitors containing different functional groups were analyzed using cyclic potentiodynamic polarization to determine their effect on the pitting potential of carbon steel reinforcements in a 0.1 M Cl– contaminated simulated concrete pore solution. It was found that organic compounds with π–electrons in a functional group had better performance. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…E HOMO (−2.88 eV) provides insight of the ability of a molecule to donate an electron to vacant cation orbital, while E LUMO (5.76 eV) indicates the ability of a structure to accept an electron creating a feedback bond [ 12 , 51 ]. A high E HOMO along with a low E LUMO are often associated with enhanced ability of the corrosion inhibitor to adsorb onto the metal surface, thus imparting superior corrosion inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…E HOMO (−2.88 eV) provides insight of the ability of a molecule to donate an electron to vacant cation orbital, while E LUMO (5.76 eV) indicates the ability of a structure to accept an electron creating a feedback bond [ 12 , 51 ]. A high E HOMO along with a low E LUMO are often associated with enhanced ability of the corrosion inhibitor to adsorb onto the metal surface, thus imparting superior corrosion inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…A high E HOMO along with a low E LUMO are often associated with enhanced ability of the corrosion inhibitor to adsorb onto the metal surface, thus imparting superior corrosion inhibition. The difference between E HOMO and E LUMO would be the Δ E gap ( E LUMO − E HOMO = 8.64 eV), which gives an indication of the reactivity of a molecule [ 12 , 52 ]. A low Δ E gap is favorable since low energy will be required to put the molecule in an excited stage, thus affecting the chemical reactivity, kinetic stability, and polarizability of a molecule [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that the electron density did not vary greatly over the molecules, leading to flat adsorption on the metal surface with contact of each atom. However, for the NO 3 − , the charge difference was greater, with a positive MAC located on the central N atom due to the resonance of the π-bonding between the N and the O atoms which have a higher electron affinity [42]. The highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) surfaces are shown in Figure 11.…”
Section: Resultsmentioning
confidence: 99%